ANALISIS TECHNOLOGY ACCEPTANCE MODEL (TAM) TERHADAP PENGGUNAAN SISTEM INFORMASI MANAJEMEN ANGGARAN DAN AKUNTANSI KEUANGAN DAERAH (SIMAKDA) DI DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI KALIMANTAN BARAT - B1031141060, Yuni Kusuma Wati B1031141060 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
This study aimed to analyze of Technology Acceptance Model (TAM) on the use of Sistem Informasi Manajemen Anggaran dan Akuntansi Keuangan Daerah (SIMAKDA) at Department of Industry and Trade of West Kalimantan Province. TAM model was developed using by including three external variables that job fit, experience and complexity. The sample in this study that the department of finance and treasurer staff whom determined by using  purposive sampling and were collected through questionnaires amounted to 32 people. Data analysis method used in this research is SEM-PLS with the help of SmartPLS 3.0. The result showed that there are some external variables which don?t have significant influence to Perceived Ease of Use and Perceived Usefulness. Therefore this research results are new since it?s different from previous research done by Tjhai (2003), Amoroso (2009), Suseno (2009), Nelvia (2009), and Hanif (2017).